Ruínas de igrejas: as representações estéticas e culturais no cerrado goiano - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The ruins of religious temples constitute na important field of aesthetic experimentation and academic possibilities. This research sought to present how the tuins in Goiás are imbued with aesthetics, history and culture. The central problem of the research consists in the analysis of na important cultural change that took place in contemporary times: why the ruins of churches in Goiás were considered a symbol of decadence, in the 19th century, but came to be valued as historical heritage and aesthetic artifacts at from the 20th century? The ruins werw seen as a symbol of decadence because they reinforced the representation of a society in civilization decline; but the 20th century onwards, the ruins were culturally valued as a historical heritage and aesthetically as na expression of the sublime. With the mergenceof the notion of historical and artistic heritage, the old began to be valued, which was also made possible by the emergence of post-moder contexto f aesthetic and cultural valorization of things fron the past. Thus, it can be seent that the cultural value of the churches in Goiás lies in the fact that these buildings went fron being devalued, because yhey represented civilizational decadence, to having aesthetic, cultural and symnolic representation recognizes by heritage bodies and society. The main objective of the research Will be to analyze the aestetic and cultural representations of the ruins of churches in Goiás, highlighting the historical and cultural transformations, and the transformations of the ruins of “symbol of decadence” in object of aesthetic valuation, seeking to analyaze the churches from the point of view of view of it is religiousm patrimonial. The first chapter sought to understand how society in Goiás conceived catholic temples in order to better measure the social value of churches that were turned into ruins. For the society goiana, for many years, the architectural ruins were seen as an argument of a decadence that reached the Province after the depletion of the gold mines in the beginning of the 19th century. In the case of the ruins of churches, the impact was much more profound, since the temples were centers of religiosity and sociability, In the second chapter, the attempt was to present that these spaces came to be valued by by the society of the 20th and 21st century through the patrimonialization of the old buildings in fragmentation. The new researches are on the way to a clearer understanding of what is the aesthetics of ruins. It is also advanced that history and patrimonialization in Goiás is much more linked to “conflicts” and political interests than to valorization itself. Finally, the last chapter sought to present the perceptions about the aesthetics of the ruins and haw the visiono f this space was of this space was being modified mainly throughout the 21st century, whem it started to be present in photographs and audiovisual productions, and howthe sublime was gaining new forms and perceptions ober the centuries. The ruins, in their various degrees of ruin, started to have differet representations for both the civil community and the artistic and academic community.
Church ruins: aesthtetic and cultural representations in the cerrado goiano
Keywords: Patrimônio - Estética; Patrimônio - História; Patrimônio - Cultura; GEOGRAFIA HUMANA::GEOGRAFIA URBANA; CIENCIAS HUMANAS::HISTORIA; ARQUITETURA E URBANISMO::PAISAGISMO